A novel approach to using modern portfolio theory - Taariq G. H. Surtee; Imhotep Paul Alagidede (Borsa İstanbul Review, 2023)
Since their inception, modern portfolio theory (MPT) and the Sharpe ratio have been among the most popular investment methodologies. Although MPT has shortcomings, it effectively uses market sentiment to predict low-risk, high-earning portfolios. Our study reviews the current practice of using the Sharpe ratio or its derivative, the Sortino ratio, and suggests that investors could earn higher returns using Sterling and Treynor ratios, instead. We find that these two ratios offer higher-performing portfolios, and their statistical distributions have indicators that assist investors in determining when to use them. These new methods outperform current indexes and funds and are more robust than the capital asset pricing model used to evaluate investment performance. We conclude by suggesting additional research with different Sterling and Treynor ratios and advanced optimization algorithms.
Keywords: C15; G11; G15; G41; 330; Modern portfolio theory; Portfolio screening; Risk-reward ratios